Emerging Concepts and Human Trials in Alpha-1-Antitrypsin Deficiency Liver Disease - Teckman, Jeffrey H. (Seminars in Liver Disease, 2017)
In α-1-antitrypsin (AAT) deficiency, individuals homozygous for the AAT mutant Z gene synthesize large quantities of mutant Z protein in the liver, which folds improperly during biogenesis and is retained within the hepatocytes rather than appropriated secreted. This accumulation of mutant Z protein triggers an intracellular injury cascade causing cell death in the population of hepatocytes with the largest accumulations of Z protein. Hepatocellular proliferation, hepatic fibrosis, and hepatocellular cancer in some individuals can be the result. New insights from basic science studies have now allowed the application of new biotechnologies to this previously untreatable disease. Specifically, drugs designed to accelerate the intracellular removal of the mutant Z protein (autophagy enhancers) and siRNA strategies designed to shut down synthesis of the toxic, mutant Z protein, are now in human trials. Other approaches, such as gene correction, cell therapy, and antifibrotic drugs are in preclinical development.
Keywords: alpha-1-antitrypsin; autophagy; liver disease; siRNA; endoplasmic reticulum-associated degradation